The Relationship between Time Management and Academic Procrastination in Students of the Faculty of Nursing - Nursa'adah, Siti; Issroviatiningrum, Retno; Abdurrouf, Muh. (Journal of Pedagogy and Education Science, 2025)
During lectures, students must manage increasing assignments, leading to delays in task completion. Academic procrastination is the intentional postponement of tasks, influenced significantly by time management. This quantitative cross-sectional study analyzes the relationship between time management and academic procrastination among 141 Nursing Faculty students at Sultan Agung Islamic University, Semarang. Using simple random sampling, data were collected via questionnaires on time management (24 statements) and procrastination (14 statements). Spearman rank correlation analysis found most respondents had moderate time management (70.2%) and procrastination levels (72.3%). A significant negative correlation was identified (p = 0.000, r = -0.383), indicating that better time management reduces academic procrastination.